Thermally activated deformation of nanocrystalline and coarse grained CoCrFeNiMn high entropy alloy in the temperature range 4.2–350 K - Podolskiy, A.V.; Schafler, E.; Tabachnikova, E.D.; Tikhonovsky, M.A.; Zehetbauer, M.J. (Физика низких температур, 2018)
Mechanical properties of a nanocrystalline (~ 60 nm) and a coarse grained (grain sizes ~ 4 µm) CoCrFeNiMn high entropy alloys were studied in uniaxial compression in the temperature range 4.2–350 K. Temperature dependences of yield strength, flow stress and strain rate sensitivity have been registered and analyzed in the framework of two thermal activation deformation models, that of thermal activation of local barrier overcoming, and that of Peierls valley double kink formation. Microscopic parameters of dislocation interaction with the barriers for thermally activated motion are estimated and low temperature deformation mechanisms are discussed. Механічні властивості нанокристалічного (середній розмір зерен ~ 60 нм) та крупнозернистого (середній розмір зерен ~ 4 мкм) високоентропійного сплаву CoCrFeNiMn вивчались шляхом одноосного стискання в інтервалі температур 4,2–350 К. Температурна залежність межі плинноcті, напруження течії та швидкісної чутливості деформуючого напруження виміряно та проаналізовано в рамках двох термоактиваційних моделей: моделі взаємодії дислокацій з локальними бар’єрами та моделі Пайєрлса щодо утворення подвійних перегинів. Визначено мікроскопічні параметри взаємодії дислокацій з бар’єрами при термоактивованому русі та обговорюються низькотемпературні механізми, які контролюють пластичну деформацію. Механические свойства нанокристаллического (средний размер зерен ~ 60 нм) и крупнозернистого (средний размер зерен ~ 4 мкм) высокоэнтропийного сплава CoCrFeNiMn изучались путем одноосного сжатия в интервале температур 4,2–350 К. Температурная зависимость предела текучеcти, напряжения течения и скоростной чувствительности деформирующего напряжения измерены и проанализированы в рамках двух термоактивационных моделей: модели взаимодействия дислокаций с локальными барьерами и модели Пайерлса образования двойных перегибов. Определены микроскопические параметры взаимодействия дислокаций с барьерами при термоактивированном движении и обсуждаются низкотемпературные механизмы, которые контролируют пластическую деформацию.